1999
DOI: 10.1515/cclm.1999.048
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Acute Phase Response and Infection. The Role of Procalcitonin and C-Reactive Protein

Abstract: Due to the significant differences in the degree of increase, PCT appears to be useful in discriminating between acute phase response following cardiac surgery with CPB or local problems and systemic infections, with additional CRP-measurement increasing the specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
2
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 26 publications
5
53
2
6
Order By: Relevance
“…Until now it has been difficult to recommend universal cut-off points for PCT, which clearly differentiate a normal from a complicated postoperative course. In the literature the cut-off points range from 1 ng/ml to 5 ng/ml [16,21,22]. Sponholz et al [16] advise interpreting PCT levels according to the clinical context.…”
Section: Discussionmentioning
confidence: 99%
“…Until now it has been difficult to recommend universal cut-off points for PCT, which clearly differentiate a normal from a complicated postoperative course. In the literature the cut-off points range from 1 ng/ml to 5 ng/ml [16,21,22]. Sponholz et al [16] advise interpreting PCT levels according to the clinical context.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Outcomes also vary for CRP in postoperative cohort studies. In one study, elevated CRP levels were detected in patients who developed systemic infections following surgery, 19 however, most studies revealed that CRP is not a useful predictor of sepsis in patients following surgical intervention: Plasma CRP concentrations were high in almost all infectious and noninfectious systemic processes. [20][21][22] Measurement of acute-phase derivative markers, such as PCT and CRP, is timeconsuming, costly, and not widely available.…”
Section: Introductionmentioning
confidence: 96%
“…Because the suspicion of sepsis in the neonate is often based on non-specific clinical signs, several predictive laboratory parameters have been investigated, including white blood cell count, tumor necrosis factor, interleukin-6, serum amyloid A, procalcitonin and C-reactive protein (CRP) (4)(5)(6)(7)(8). Serial CRP measurements are also used to monitor the evolution of bacterial diseases because CRP concentration drops quickly in response to effective treatment (9). Monitoring CRP concentration can lead to shorter antibiotic regimens or, alternatively, can alert one to the likelihood of complications and help predict outcome, even earlier than clinical signs (10).…”
Section: Introductionmentioning
confidence: 99%